INNOVATION AND COMPETITIVENESS IN LIGHT INDUSTRY (Modern education and development, 2025)
This article is devoted to the topic “Innovation and competitiveness in light industry” and analyzes the importance of innovative processes in light industry in increasing the competitiveness of companies. The light industry, with its dynamics and rapid variability, is achieving success through the introduction of modern technologies and innovative solutions. The article examines key areas of innovative activities, including new materials, digital technologies, sustainable production and adaptation to customer needs.